Monitoring Kondisi Tegangan Accu Dengan Menggunakan Komunikasi Bluetooth HC-05 Dengan Smartphone Android - ., Bambang Ermanto (Jurnal Teknik Elektro Universitas Tanjungpura, 2016)
One of the reasons for the emergence of a monitoring system battery voltage condition is the need of people in appropriate technology that can make the job run quickly and reduce the risk of damage to the accu. Accu is a tool to store electrical energy in chemical form. It was used to supply power to lights and other electrical components. The problem was the user does not know the condition of accu that has reached a voltage level below the average. For example, for dry accu, the voltage level for the bad condition was recommended until the voltage is 10.5 volts. In this final project, it was designed a monitoring system of accu voltage condition with Bluetooth hc - 05 with android smart phone from a range of 10 meters. Another important thing is the component of the regulator voltage value generated by the good condition of the accu is the range of 13.4 V - 14.8 volts. It has been done a design of electronic devices that can monitor the condition of accu voltage; the information of accu flow was processed by a microcontroller ATmega16 and displayed on Android smart phone that we can bring easily. So that, the users will be able to know the accu condition directly without open the accu place to see the condition of the electrical.      Keywords: Bluetooth Hc-05, Voltage Sensor, Flow Sensor, Microcontroller, ATMega 16, Android Smartphone